Effect of Oxidative Stress on Diaphragm Dysfunction and Exercise Intervention in Chronic Obstructive Pulmonary Disease - Zhang, Bingzhi; Li, Peijun; Li, Jian; Liu, Xiaodan; Wu, Weibing (Frontiers in Physiology, 2021)
Chronic obstructive pulmonary disease (COPD) can cause extrapulmonary injury such as diaphragm dysfunction. Oxidative stress is one of the main factors causing diaphragm dysfunction in COPD. Exercise plays a positive role in the prevention and treatment of diaphragm dysfunction in COPD, and the changes in diaphragm structure and function induced by exercise are closely related to the regulation of oxidative stress. Therefore, on the basis of the review of oxidative stress and the changes in diaphragm structure and function in COPD, this article analyzed the effects of exercise on oxidative stress and diaphragm dysfunction in COPD and explored the possible mechanism by which exercise improves oxidative stress. Studies have found that diaphragm dysfunction in COPD includes the decline of muscle strength, endurance, and activity. Oxidative stress mainly affects the structure and function of the diaphragm in COPD through protein oxidation, protease activation and calcium sensitivity reduction. The effects of exercise on oxidative stress level and diaphragm dysfunction may differ depending on the intensity, duration, and style of exercise. The mechanism of exercise on oxidative stress in the diaphragm of COPD may include improving antioxidant capacity, reducing oxidase activity and improving mitochondrial function.